2021
DOI: 10.33225/jbse/21.20.10
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Math and Science Exposure on the Effect of 5e Instructional Model in Physics Conceptions

Abstract: 5E instructional model is commonly utilized in science teaching to promote conceptual learning. However, the benefit of 5E instructional model cannot be fully attained if the knowledge and skills essential to learning were not properly established from past. Similarly, the development of new concepts cannot be fully attained if the important processes inculcated in the 5E model were not considered in teaching. In this research, the effects of 5E model instruction and previous learning experiences on the concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
7
0
3
Order By: Relevance
“…This finding is consistent with the findings of Omotayo and Adeleke [24] who discovered a significant difference between the experimental group and the control group after the experimental group was exposed to the 5E instructional model in favour of the experimental group. The following studies highlight similar findings that indicate that the 5E instructional model improves students' academic performance in Mathematics [13,12,25,23]. .000…”
Section: Achievement Of Students In Control and Experimental Groupssupporting
confidence: 60%
“…This finding is consistent with the findings of Omotayo and Adeleke [24] who discovered a significant difference between the experimental group and the control group after the experimental group was exposed to the 5E instructional model in favour of the experimental group. The following studies highlight similar findings that indicate that the 5E instructional model improves students' academic performance in Mathematics [13,12,25,23]. .000…”
Section: Achievement Of Students In Control and Experimental Groupssupporting
confidence: 60%
“…However, the 5E teaching model is flexible and can be used with many different types of teaching resources, programs, and materials that teachers may already have (Chitman-Booker & Kopp, 2017). The 5E teaching model, which encourages conceptual learning, is widely used in science teaching (Bahtaji, 2021). Data from a study by Budprom et al, (2010) also showed that the 5E educational model increased students' SPS levels.…”
Section: Discussionmentioning
confidence: 99%
“…Model 5E pertama kali diciptakan oleh Atkon dan Karplus pada tahun 1962 (Ong et al, 2020). Model pembelajaan ini dikembangkan dari teori konstructivisme yang berpandanagn bahwa setiap orang belajar dengan cara mengkonstruksi pengetahuannya berdasarkan pengalaman dalam berinteraksi dengan lingkungan (Bahtaji, 2021) (Ong et al, 2020). Penelitian yang dilakukan oleh Bahtaji pada mata pelajaran Matematika menyatakan bahwa penerapan model 5E menyajikan pengalaman nyata yang membantu peserta didik dapat merestrukturisasi pengetahuan yang sudah mereka dapat sebelumnya (Bahtaji, 2021) (Arikunto, 2015) (Suryadi & Berdiati, 2018).…”
Section: Pendahuluanunclassified